2015
DOI: 10.1038/cr.2015.108
|View full text |Cite
|
Sign up to set email alerts
|

Siglec1 suppresses antiviral innate immune response by inducing TBK1 degradation via the ubiquitin ligase TRIM27

Abstract: Type I interferon (IFN) production plays pivotal roles in host antiviral innate immune responses, but an excessive production of type I IFN leads to the development of immunopathological conditions. Investigations on the regulatory mechanisms underlying host type I IFN production are currently of great interest. Here, we found that the expression of lectin family member Siglec1 was upregulated by viral infection in macrophages, which was dependent on the IFN/JAK/STAT1 signaling pathway. Siglec1 was found to ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
121
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(129 citation statements)
references
References 41 publications
(51 reference statements)
3
121
1
1
Order By: Relevance
“…Siglecs which lack an ITIM domain (such as Siglec-14, 15, and 16) associate with DAP12 via a positively charged amino acid in their transmembrane region to activate receptors through the recruitment of Syk (15,40). Siglec-1, the first discovered member of Siglecs, has been shown to play an important role in sialylated pathogen uptake (17,19,(53)(54)(55), antigen presentation (56,57), lymphocyte proliferation (58), self-tolerance (59,60) and antiviral immune response (47). However, the biological function of Siglec-1 in endotoxin tolerance is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Siglecs which lack an ITIM domain (such as Siglec-14, 15, and 16) associate with DAP12 via a positively charged amino acid in their transmembrane region to activate receptors through the recruitment of Syk (15,40). Siglec-1, the first discovered member of Siglecs, has been shown to play an important role in sialylated pathogen uptake (17,19,(53)(54)(55), antigen presentation (56,57), lymphocyte proliferation (58), self-tolerance (59,60) and antiviral immune response (47). However, the biological function of Siglec-1 in endotoxin tolerance is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that Siglec-1 is associated with DAP12 in VSV-infected macrophages to control the antiviral innate immune response (47). We next examined whether Siglec-1, DAP12, and Syk form a complex to regulate the production of TGF-␤1 in RAW 264.7 cells after induction of endotoxin tolerance.…”
Section: Down-regulation Of Siglec-1 Promotes Degradation Of Syk By Imentioning
confidence: 99%
“…Interestingly, we previously found that Siglec1 and TRIM27 are negative regulators of VSV-triggered type I IFN production (11). Phenocopying the effect of miR-27a overexpression, both Siglec1 and TRIM27 knockdown significantly increased VSV-triggered type I IFN production and accordingly inhibited VSV replication (11).…”
Section: Antiviral Function Of Mir-27a Is Mainly Through Targeting Simentioning
confidence: 99%
“…For example, sialic acid-binding Ig-like lectin (Siglec)-G negatively regulates type I IFN production in the innate response against RNA virus infection by promoting retinoic acid-inducible gene I (RIG-I) proteasomal degradation (10). We previously found that Siglec1 associated with DNAX activation protein-12 to activate the scaffolding function of Src homology 2 domain-containing protein tyrosine phosphatase 2, and then recruited E3 ligase tripartite motif-containing protein 27 (TRIM27) to degrade TBK1, thus negatively regulating type I IFN production (11). Hence, type I IFN production during viral infection should be tightly controlled to initiate an appropriate immune response that eliminates invading pathogens but to avoid excessive production of type I IFN-mediated immunopathological conditions or immune disorders (12,13).…”
mentioning
confidence: 99%
“…For example, DNA methyltransferase Dnmt3a selectively upregulates the production of type I interferons by maintaining high expression of HDAC9 to deacetylate TBK1 for activation of antiviral innate immunity . RNA viruses can specifically upregulate the expression of Siglec-G (Chen et al, 2013b), Siglec1 (Zheng et al, 2015) and DAPK1 (Zhang et al, 2014a) which regulate antiviral innate immune response. Cytoplasmic STAT4 has been described to interact with E3 ligase CHIP and block RIG-I and CHIP association, resulting in preventing CHIP-mediated proteasomal degradation of RIG-I .…”
Section: Regulation Of Rlr Signaling Pathwaysmentioning
confidence: 99%